Development of Unmanned Aerial Vehicle for Detecting the Forest Fires - KADIOĞLU, Barış Mert; KARATAY, Seçil; ÇETİNCEVİZ, Yücel; ERKEN, Faruk (Firat Universitesi, 2023)
In recent years, forest fires can be brought under control in line with the information obtained from Unmanned Aerial Vehicles (UAVs), which play an important role in determining the progression of fires, detecting heat points and determining intervention locations. In this study, if the UAV detects the fire by autonomously positioning in the area where the fire is located, the point where the fire reaches the most intense temperature is determined with the help of the thermal camera, and it is ensured that the fireball is dropped to the target with a 100% success rate. The requirements of the UAV, which will be produced in order to realize this task, such as fast, load-carrying and stable flight are also taken into consideration. In addition to being economical and long-lasting of the materials inside, it will be able to fly efficiently in most weather conditions (foggy, dark, etc.). In the construction of the UAV, a domestic Electronic Speed Controller (ESC) with a unique design is produced to meet the sufficient current. With this acquisition, ESC, which will meet the requirements by sending sufficient current to more than one Brushless DC (BLDC) motor, has been tested on our Radio Controlled (RC) aircraft and included in the project.
Keywords: 15. Life on land; 7. Clean energy